The utilization of auto-inducible Plyb promoter and media optimation for cell density-dependent expression of recombinant xylanase in Bacillus subtilis DB104 - Haniyya Haniyya; Dini Achnafani; Maria Ulfah; Niknik Nurhayati; Is Helianti (Indonesian Society for microbiology, 2020)
Strong promoters are one of the fundamental aspects to increase the level of gene expression, and one of approach to improve the recombinant enzyme productivity so that the efficiency of production cost for enzyme production in industrial scale can be reached. Here we assessed the application of a cell density-dependent promoter and media optimation to promote cell growth and protein expression of Bacillus subtilis without excess usage of inducers. An auto-inducible Pylb promoter that is potential to provide inducer-free enzyme production was cloned and introduced into xylanase recombinant system in B. subtilis DB104 by PCR cloning and protoplast transformation. A 200 bp target gene was successfully inserted in between xynCM1 ORF -coding for B. halodurans CM1 xylanase- and its native promoter sequence at the upstream region. The disruption of the native promoter was intended to replace the native promoter with Pylb. Recombinant xylanase gene under Pylb was successfully expressed in B. subtilis DB104 and the enzyme was produced at stationary phase. Different media with various concentrations of glucose and nitrogen were used to optimize recombinant xylanase expression. It achieved a higher level of xylanase expression compared to wild-type and recombinant xylanase with native promoter B. subtilis in media containing a 2-fold recipe of LB media thus leads to increase cell density and xylanase expression (81.461 U mL-1).